A need for new accident theories in Malaysia? - Dhanabal, Saravanan; Karuppiah, Karmegam; Mani, Kulanthayan K.C.; Rasdi, Irniza; Sambasivam, Sivasankar (Malaysian Public Health Physicians' Association, 2016)
Workplace accident is a big challenges for a safety professional. Workplace accidents may lead from minor to serious effects to both employees and employers alike. Accident is an unexpected and undesirable event, especially those resulting in damage, harm or unforeseen incidents. This paper also discussed all available accident theories that are commonly used in workplace as fundamental to mitigating accident. Throughout this paper, the author justified that a new or updated accident theory is needed in Malaysia. The author stated that current accident theories are based on different environments and are different in terms physical of the employee who involved in the accident. This author also stated that technology changes is also another factor which can be supporting the new or updated accident theory needed in Malaysia.